Harry, the dirty dog - Zion, Gene.; Graham, Margaret Bloy (New York : HarperCollins, 1984)
When a white dog with black spots runs away from home, he gets so dirty his family doesn't recognize him as a black dog with white spots.
AD 700
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction